The influence of special graduated weight load in Greco-Roman wrestling on the growth of students’ sports results - R.S. Nagovitsyn; P.B. Volkov; A.A. Miroshnichenko; A.A. Tutolmin; S.Yu. Senator (Physical Education of Students, 2017)
Aim: to assess the impact of a special dosage load in Greco-Roman wrestling on the growth of students’ sports results. Materials and methods: in research participated 2-3 courses students (n=29, age 16-19 years). The students were divided into two groups: experimental (EG, n=14) and control (CG, n=15). All students were engaged in 4 times per week for 2 hours. Complexes of technical-tactical and psychophysical tasks in the process of each training are realized for 7 - 7,5 minutes (with a break of 30 seconds). Results. A special diagnostic toolkit has been developed to monitor the effectiveness of wrestlers’ training in three indicators: physical, intensive and effective. It was revealed that in order to intensify the intensity of the competitive duel, a special loading dosage should be used. It is established that performing exercises with weights without taking into account the special loading dosing leads to a decrease in the speed of the wrestler’s movements and to a slowing down of the tempo of the fight. At maximum speed-strength exercise, the athlete’s ability to concentrate on coordinating his performance (on the technique of performing the exercise during a competitive duel) is lost. Conclusions: In case of a maneuver attack, wrestlers play out their opponent with false and preparing attacks. The technique of attacking style requires fast, sharp movements of the body with the capture of the opponent. Therefore, it is advisable to train an athlete in the conduct of a duel using the weight of his own body.